High thermal and electrochemical stability of PVDF-graft-PAN copolymer hybrid PEO membrane for safety reinforced lithium-ion battery. Issue 22 (12th February 2016) - Hsu, Chang-Yu; Liu, Ren-Jun; Hsu, Chun-Han; Kuo, Ping-Lin
Abstract : A PVDF- graft -PAN copolymer was prepared by ozone polymerization and hybrid with PEO as a conductive gel–polymer electrolyte for lithium-ion batteries. Abstract : A polyvinylidene fluoride- graft -polyacrylonitrile (PVDF- g -PAN) copolymer was prepared by ozone polymerization and characterized by 1 H-NMR. The as-prepared copolymer is a hybrid with polyethylene oxide (PEO), named m-PVDF, and was applied as a conductive gel–polymer electrolyte for lithium-ion batteries. According to morphology analysis, the m-PVDF membrane has less microphase separation than the PVDF blending with the PAN and PEO system (b-PVDF) which means that the PVDF- g -PAN copolymer can increase the compatibility of PVDF and PEO polymers. From the DSC analysis, introduction of PVDF- g -PAN effectively decreases the crystallinity of the PEO polymer in the m-PVDF membrane, which assists in lithium-ion transport. Moreover, m-PVDF shows high thermal stability up to 400 °C and good dimensional-stability under 150 °C, which can prevent the batteries from short-cutting and burning as well as other safety problems at high temperature. For battery application, the membrane shows good electrochemical stability up to 5 V ( vs. Li/Li + ). Furthermore, cells incorporating the m-PVDF membrane demonstrated remarkably excellent capacity retention with a capacity decay of only 9.1% after 300 cycles. Accordingly, these results suggest that the introduced PVDF- g -PAN significantly improved the electrolyte compatibility, thermal properties and wettability of the membrane, yielding a high-performance and high-safety electrolyte.